Effects of the geometrical configuration of air–water mixer on the size and distribution of microbubbles in aeration systems - Basso, Alessio; Hamad, F.A.; Ganesan, Poo Balan (Wiley, 2018)
The objective of this work is to present a novel geometrical configuration for microbubble generators (MBGs) to improve dissolved-oxygen levels in water. Among various methodologies from the literature, Orifice and Venturi tubes have been considered as baseline cases. Experimental data from the literature are used to verify a computational fluid dynamics (CFD) case developed for a better understanding of the dynamics of MBGs. As a result, the validated CFD setup has been implemented on a modified Venturi-type generator, where air is injected coaxially with respect to the tube axis, whereas a helicoid wall at variable pitch angle is used. Results show a reduction in the mean bubble diameter distribution from the baseline Venturi tubes, particularly, at low-speed inlet velocities. This is of interest, especially to decrease the energy requirement for most common water aeration systems.